Principles and Constants of the Golden Proportion as a Criterion in Donosological Diagnostics of the Functional States of The Body and in the Assessment of the Probability of their Changes - Karabayev, M.; M. Gasanova, N.; T. Botirov, M.; Kosimova, G.S. (International Physiology Journal, 2022)
A theoretical paper proposes applications of golden proportion principles to physiological diagnostics. It outlines proposed metrics and discusses validation needs and limitations.
Keywords: functional state; adaptive potential; health levels; golden ratio constants; harmonization; optimization; assessment scale.